Histerectomía abdominal total a paciente por miomatosis uterina con enfoque en el proceso de atención de enfermería - Conde Sarango, Ana Maria (Machala : Universidad Técnica de Machala, 2018)
Introduction: The uterus is a hollow muscular organ that is located in the female pelvis, between the bladder and the rectum. It is also considered a site of many conditions, both benign and malignant. The giant uterine myoma is a benign tumor of very low incidence. Its resolution represents a challenge for medical and nursing staff, due to the variability in clinical manifestations that range from asymptomatic to severe symptoms that involve neighboring organs due to uterine growth and in effect due to the large volume of the surgical piece. Rarely, these tumors become malignant (<1%). Although to date it has not been detailed with certainty the causes that produce the appearance of fibroids in the uterus, other authors mention in their publications that there are risk factors related to this pathology of a benign nature, such as: age, overweight or obesity, nulliparity, estrogen-producing ovarian tumors and any other condition that increases exposure to estrogens and progestogens during the reproductive age of these women. In researches conducted by twentieth century scientists, reveal that the weight of the "giant" myoma, to be considered as such, should weigh more than 2 kg, for the reason given, the treatment of choice is hysterectomy. Presentation of the Case: A 44-year-old patient admitted on 6/12/2017 to a hospital ward with a request for hospitalization with a medical diagnosis of uterine myomatosis, benign ovarian tumor and moderate anemia at the Hospital Gineco-Obstétrico Angela Loayza de Ollague from the city of Santa Rosa. Vital signs: T °: 36.6ºC, TA: 100/60 mmHg, FC: 78 beats per minute, FR: 20 breaths per minute, SO2: 99%, Weight: 67.1Kg and Size: 150.7cm. The assessment refers to constipation (compression on the rectum), urination many times (compression in the bladder), nocturia, lumbar pain, globular abdomen attributable to the diagnosis, slightly painful on palpation, irregularly (asymmetric), and no evidence transvaginal bleeding. She was submitted to surgery on 8/12/2017 (Start: 12: 17- End: 13:33), where gynecologist performed a Total Abdominal Hysterectomy, obtaining after extraction, a MU of 24 cm, with a weight of 3.5 Kg The woman evolved satisfactorily after the intervention, her hospital stay was 6 days, later histopathological study confirmed that it was a giant uterine myoma. General Objective: To analyze the case of a patient undergoing Total Abdominal Hysterectomy through the assessment of the 14 needs established by Virginia Henderson and the nursing care process according to NANDA, NOC and NIC.
Introducción: El útero es un órgano muscular hueco que se ubica en la pelvis femenina, entre la vejiga y el recto. También es considerado sitio de muchas afecciones tanto benignas como malignas. El mioma uterino gigante es una tumoración benigna de muy escasa incidencia. Su resolución representa un reto para el personal médico y de enfermería, por la variabilidad en las manifestaciones clínicas que van desde asintomáticos hasta síntomas graves que comprometen a órganos vecinos por el crecimiento uterino y en efecto por el gran volumen de la pieza quirúrgica. Rara vez, estos tumores llegan a malignizarse (<1%). Aunque hasta la fecha no se ha detallado con certeza las causas que producen la aparición de los miomas en el útero, otros autores mencionan en sus publicaciones que existen factores de riesgo relacionados con esta patología de naturaleza benigna, tales como: edad, sobrepeso u obesidad, nuliparidad, tumores ováricos productores de estrógenos y cualquier otra condición que aumente la exposición a estrógenos y progestágenos durante la edad reproductiva de estas mujeres. En las investigaciones realizadas por científicos del siglo XX, revelan que el peso del mioma “gigante”, para ser considerado como tal, debe pesar mayor de 2 kg, por la razón expuesta, el tratamiento de elección es la histerectomía. Presentación del Caso: Paciente de 44 años de edad que ingresa el 6/12/2017 a sala de hospitalización con solicitud de internación con diagnóstico médico de Miomatosis uterina, Tumor benigno de ovario y Anemia Moderada, en el Hospital Obstétrico Ángela Loayza de Ollagüe, de la ciudad de Santa Rosa. Signos vitales: T°: 36.6ºC, TA: 100/60 mmHg, FC: 78 lpm, FR: 20 rpm, SO2: 99%, Peso: 67.1Kg y Talla: 150.7cm. A la valoración refiere estreñimiento (compresión sobre el recto), orina muchas veces (compresión en la vejiga), nicturia, dolor lumbar, abdomen globuloso atribuible al diagnóstico, ligeramente doloroso a la palpación, de forma irregular (asimétrico), y no se evidencia sangrado transvaginal. Fue sometida a quirófano el 8/12/2017 (Inicio: 12:17- Fin: 13:33), donde ginecólogo le realizó una Histerectomía Abdominal Total, obteniéndose tras la extracción, un MU de 24 cm, con un peso de 3.5 Kg. La mujer evolucionó satisfactoriamente después de la intervención, su estancia hospitalaria fue de 6 días, posteriormente estudio histopatológico confirmó que se trataba de un MU gigante. Objetivo General: Analizar el caso de una paciente sometida a Histerectomía Abdominal Total mediante la valoración de las 14 necesidades que establece Virginia Henderson y el proceso de atención de enfermería según la NANDA, NOC y NIC.
Keywords: MIOMATOSIS UTERINA; LEIOMIOMA DEL UTERO; HISTERECTOMIA; PROCESO DE ATENCION DE ENFERMERIA